Deliberate practice in training differentiates the best Kenyan and Spanish long-distance runners - Casado, A.; Hanley, B.; Ruiz-Pérez, L. M. (European Journal of Sport Science, 2020)
The aim of this novel research was to compare the amount of systematic training and the different training activities undertaken by elite-standard long-distance runners during their first seven years of systematic training. Participants were divided into three performance groups: world-class Kenyans (N = 19), European-standard Spanish athletes (N = 18), and Spanish national-standard athletes (N = 18). Performance and training data were obtained for two-year periods using retrospective recall (including training diaries) from the time the athletes began systematic training, until the seventh year after. These activities included high-intensity training sessions considered deliberate practice (DP) and easy runs. There was no evidence that starting systematic training at a younger age was advantageous, and easy runs (a non-DP activity) were the most used by participants as a proportion of overall running distance. As part of an overall higher accumulation of distance run (P < 0.001, d = 1.35), the Kenyans completed more tempo runs and short-interval training than the other groups (P < 0.001, d = 1.38), but did not complete more long intervals or races. There were few differences between the European- and national-standard athletes except for easy runs, which highlights the value of these easy runs but also the need for higher-intensity training to compete with world-class performers. When planning for training overload and progression, long-distance running coaches should consider increasing the volume of tempo runs and short intervals, in addition to easier runs that develop cardiovascular conditioning.